Emerging non-destructive methods for quality and safety monitoring of spices. (February 2021) - Modupalli, Nikitha; Naik, Mohan; Sunil, C.K.; Natarajan, Venkatachalapathy
Abstract: Background: The growing concerns about food quality and safety among consumers have increased the need for food authentication, which can be a powerful tool to combat different types of food frauds in the supply chain. Spices are recognised as high-value products and often adulterated like other agricultural commodities, which can pose a serious health risk and economic damage. Therefore, rapid, precise, accurate and up-to-date sophisticated analytical methods are the prerequisite to detect adulterations/frauds in spices. Scope and approach: The officially approved laboratory analytical testing methods for spices are time consuming and destructive. These limitations can be alleviated by search of rapid and precise non-destructive quality testing methods. The fact that spectroscopic, acoustic, and ultrasound and artificial sensing techniques have immense food quality testing and safety monitoring applications. Spectroscopy measures the electromagnetic radiation emits by substrates and uses the data to determine its properties, whereas artificial sensing methods replicate the human sensory responses mechanically. This review will present the emerging non-destructive quality testing methods used to authenticate spices, including determining the origin, identifying adulterants and contaminants. Moreover, challenges and future trends in spice authentication using non-targeted evaluation have been addressed. Key findings and conclusions: The non-destructive techniques have been proven to be useful tools for the quality and safety monitoring of spices. The advances in the spectroscopy and e-sensing techniques have made the detection of adulteration in spices in a precise and fail-proof way, and have been efficient in authenticating the spices. Their utility in evaluating the quality and safety of spices needs to be improved using the new-age data analytics like big data and simplified into hand-held systems for efficient and simplified use. Highlights: Non-destructive quality testing is a powerful aid that helps in monitoring the quality of spices. Spectroscopy and artificial sensing methods have led development in real-time safety monitoring throughout the supply chain of spice products. Data analytics and chemometrics approaches help in analysing the information obtained to establish the relationship between samples. Hyperspectral imaging and nuclear magnetic resonance give elaborate information about the spatial orientation of the samples.